KEPATUHAN INDONESIA TERHADAP REZIM ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION (AATHP) - Rani Nova Yusra (Frequency of International Relations (FETRIAN), 2019)
The aim of this research is to analyse Indonesia’s compliance with the ASEAN Agreement on Transboundary Haze Pollution (AATHP) regime, where Indonesia as the main actor in cross-border smoke haze pollutions is in the spotlight in every forest fire that occurred in the Southeast Asia region which resulted in cross-border smog. This research is a qualitative research with data collection techniques namely internet-based literature study. The analysis in this research uses international regime theory and regime compliance with indicators of outputs, outcomes and impact. From the result of the analysis in this research, it can be concluded that Indonesia obeys the ASEAN Agreement on Transboundary Haze Pollution (AATHP) regime because Indonesia has succeeded in fulfilling the three indicators of regime compliance theory. From the outputs indicator, Indonesia has succeeded in making regulations and institutions, from the outcomes indicator which can be seen from Indonesia’s consistency in acting and implementing programs and from impacts indicator is proven by the improvement of the environment quality especially Indonesia’s forests.